Un-burnable oil: an examination of oil resource utilisation in a decarbonised energy system - McGlade, C; Ekins, P (2014)
This paper examines the volumes of oil that can and cannot be used up to 2035 during the transition to a low-carbon global energy system using the global energy systems model, TIAM-UCL and the 'Bottom up Economic and Geological Oil field production model' (BUEGO). Globally in a scenario allowing the widespread adoption of carbon capture and storage (CCS) nearly 500 billion barrels of existing 2P oil reserves must remain unused by 2035. In a scenario where CCS is unavailable this increases to around 600 billion barrels. Besides reserves, arctic oil and light tight oil play only minor roles in a scenario with CCS and essentially no role when CCS is not available. On a global scale, 40% of those resources yet to be found in deepwater regions must remain undeveloped, rising to 55% if CCS cannot be deployed. The widespread development of unconventional oil resources is also shown to be incompatible with a decarbonised energy system even with a total and rapid decarbonisation of energetic inputs. The work thus demonstrates the extent to which current energy policies encouraging the unabated exploration for, and exploitation of, all oil resources are incommensurate with the achievement of a low-carbon energy system. © 2013 The Authors.